303 Elevated risk of psychiatric disorders after occupational injury. (11th October 2013) - Guo, L; Lin,; Chu,; Kuo,; Wu,; wang, H
Abstract : Objectives: Psychiatric conditions are known to occur after traumatic injuries. This study aimed to determine the incidence rates of psychiatric disorders within one year after occupational injury and to compare the incidence of psychiatric disorders among people sustaining occupational and non-occupational injuries, and the enrollees of the National Health Insurance (NHI) without injury. Methods: We used cohort approach in this investigation. All eligible subjects were insured by the NHI of Taiwan, and aged 18–65 years old. We identified enrollees who sustained occupational injury and non-occupational injuries in 2001. Those in the reference group were patients who ever used the NHI for any medical condition in 2001. The patients who had been treated due to any injury within one year before and after the target injury/condition in 2001 and who had been treated due to psychiatric disorders within one year before the date of target injury/condition were excluded. Results: A total of 563, 461 patients were enrolled in this study. Among them, 1060 patients sustained occupational injury, 7442 patients sustained non-occupational injury, 554, 959 patients ever used NHI for any medical condition in 2001. The incidence rates of any psychiatric disorders within one year after occupational injury requiring hospitalisation, occupational injury treated as outpatient, non-occupational injury requiring hospitalisation, non-occupational injury treated as outpatient, and any disease were 10.4%, 2.5%, 8.5%, 1.5%, and 1.3%, respectively. Occupational injury was found as a significant factor for developing psychiatric disorders within one year after the target injury. Conclusion: The incidence rate of developing any psychiatric disorders was higher in patients after occupational injury than those after non-occupational injury and any medical condition. Further investigations are warranted to identify risk factors for psychiatric disorders following occupational injuries.